Chronic Intermittent Hypoxia Reduces the Effects of Glucosteroid in Asthma via Activating the p38 MAPK Signaling Pathway - Liang, Li; Gu, Xin; Shen, Hai Ji; Shi, Yu Heng; Li, Yao; Zhang, Jie; Chen, Yan Yan; Chen, Zhen He; Ma, Jia Yun; Li, Qing Yun (Frontiers in Physiology, 2021)
Aims: Obstructive sleep apnea (OSA) is a risk factor for steroid-resistant (SR) asthma. However, the underlying mechanism is not well defined. This study aimed to investigate how chronic intermittent hypoxia (CIH), the main pathophysiology of OSA, influenced the effects of glucocorticoids on asthma. Main methods: The effects of dexamethasone (Dex) were determined using the ovalbumin (OVA)-challenged mouse model of asthma and transforming growth factor (TGF)-β treated airway smooth muscle cells (ASMCs), with or without CIH. The p38 MAPK signaling pathway activity was then detected in the mouse (n=6) and ASMCs models (n=6), which were both treated with the p38 MAPK inhibitor SB239063. Key findings: Under CIH, mouse pulmonary resistance value, inflammatory cells in bronchoalveolar lavage fluid (BALF) and inflammation scores increased in OVA-challenged combined with CIH exposure mice compared with OVA-challenged mice (p<0.05). These indicators were similarly raised in the OVA + CIH + Dex group compared to the OVA + Dex group (P<0.05). CIH exposure enhanced activation of the p38 MAPK pathway, oxidative stress injury, and the expression of NF-κB both in lung tissue and ASMCs, which were reversed by treatment with Dex and SB239063. In the in vitro study, treatment with Dex and SB239063 decreased ASMCs proliferation induced by TGF-β combined with CIH, and suppressed activation of the p38 MAPK pathway, oxidative stress injury and NF-κB nuclear transcription (p<0.05). Significance: These results indicated that CIH decreased glucocorticoid sensitivity by activating the p38 MAPK signaling pathway.